The Spread and Utility of Social Network Analysis across a Group of Health Behavior Researchers - Megan S. Patterson; Tyler Prochnow; Patricia Goodson (New Prairie Press, 2019)
Social network analysis (SNA), both as theory and methodology, is a powerful framework for delimiting and studying health behaviors. Using SNA allows scholars to answer new research questions, innovatively investigate the social and systemic contexts of health and behavior, and collaborate on multi- or inter-disciplinary projects. As a result, SNA is growing in popularity within health behavior research and practice. Despite SNA's contribution and appeal, few health behavior researchers and practitioners have access to formal SNA education; much of the current training efforts occur outside degree-granting curricula. Therefore, the aims of this paper were to: 1) assess the diffusion of SNA, over time, among scholars presenting at AAHB annual meetings; and 2) determine whether AAHB can function as a professional venue for fostering development of SNA-related skills, especially by capitalizing on mentoring relationships. To assess the "spread" of SNA among AAHB scholars, we conducted a network analysis to capture the connections among those presenting research posters between 2016 and 2019. Results indicated sizeable increases in adoption of, and exposure to SNA within this network. Based on these findings, we recommend responding to the growing trends of SNA use by providing conference-based training and education in SNA. We also propose utilizing mentorship ties as leverage points in diffusing SNA within a system of professional scholars and, as a result, advancing health behavior research and practice.